A thermal spray strengthening and remanufacturing method for shallow defects of metal castings
The surface roughness of metal castings is improved through laser pretreatment, and combined with the pore sealing technology of circulating air pressure and ultrasonic treatment, the problem of pore defects inside the thermal spray coating is solved, the bonding strength and corrosion resistance are improved, and the service life of the coating is extended.
Patent Information
- Application Number
- CN202411363995.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-28
AI Technical Summary
When the existing thermal spraying technology is repaired on the surface of metal castings, pore defects inevitably exist inside the coating, resulting in low bonding strength and prone to coating peeling and corrosion.
Laser pretreatment is used to increase the roughness of the surface of metal castings, and the sealing treatment is performed using circulating air pressure and ultrasonic auxiliary sealing agent after thermal spraying to reduce the porosity of the coating.
It significantly improves the bonding strength between thermal spray coating and metal castings, extends the service life of the coating, enhances corrosion resistance, and improves the repair and strengthening effect.
Smart Images

Figure BDA0005065678380000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal surface post-processing, and more specifically, to a thermal spraying strengthening remanufacturing method for shallow surface defects of metal castings. Background Art
[0002] Due to the limitations of the manufacturing process itself, metal castings are prone to defects such as holes, cracks, inclusions, segregation, etc. on the shallow surface. These defects affect the durability of the parts under different conditions, including corrosion resistance, resistance to sudden cold and heat, fatigue, shock absorption and other performances as well as machinability, weldability and other process properties. Once defects are found in the shallow surface of a metal casting in service, they must be repaired immediately. If they are not repaired in time, as the service time of the metal casting increases, the defects will become more and more serious, and eventually develop into cracks or perforations.
[0003] Traditional repair methods include welding, cold welding, and applying metal repair agents. However, the welding repair method inputs too much heat to the metal casting, which is easy to produce thermal cracks and thermal stress, reducing the toughness and plasticity of the metal casting, and is not suitable for large-area repairs; although the cold welding repair method does not input much heat, it is only suitable for local small-area repairs, not for large-area repairs; metal repair agents are physically combined with metals, and their bonding strength is average, and they are prone to falling off, so they are only suitable for temporary repairs, not for long-term use.
[0004] With the continuous deepening of research, thermal spraying technology has become a commonly used metal surface repair and strengthening remanufacturing technology. Thermal spraying technology is to heat the spraying particles to a molten or semi-molten state through a heat source, and spray the spraying material onto the surface of the metal casting under the action of a compressed air flow. After it quickly solidifies on the surface of the metal casting, it forms a protective film to make up for the defects on the surface of the metal casting, and improves the wear resistance, corrosion resistance, high temperature resistance and heat insulation of the metal casting, so as to achieve the strengthening remanufacturing of the metal casting. However, since the protective film formed by thermal spraying technology is a layered structure that is stacked together in a wave-like manner by countless flattened particles, oxides, partially melted or unmelted particles, air and impurities, it is inevitable that some pore defects will appear inside it, and the bonding strength with the metal casting is low, and it is easy to cause the particles on the coating surface to fall off, and the coating as a whole to peel off and fail. In addition, the pore defects are also easy to cause the external corrosive medium to penetrate and diffuse into the coating, making the metal casting susceptible to various forms of corrosion, reducing the ability of the thermal spray coating to repair and strengthen the metal casting. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a thermal spray strengthening and remanufacturing method for shallow defects of metal castings.
[0006] The present application provides a thermal spray strengthening remanufacturing method for shallow defects of metal castings, which adopts the following technical solution:
[0007] A thermal spray strengthening remanufacturing method for shallow defects of metal castings, comprising the following steps:
[0008] S1. Degreasing, cleaning and laser pretreatment of metal castings;
[0009] S2. A thermal spray coating is prepared on the surface of the metal casting treated in step S1 by a thermal spraying process;
[0010] S3. Apply the sealing agent to the surface of the coating, and then ultrasonically treat it under vacuum-pressure-vacuum cycle pressure for 1-1.5 hours, wherein the vacuum environment is maintained for 5-10 minutes, and then the sealing treatment is completed through curing.
[0011] By adopting the above technical scheme, the present application first degreases and cleans the surface of the metal casting, and the specific process of the degreasing and cleaning is: first use acetone to degrease and rust the surface of the metal casting, and then clean and blow dry. Then the surface of the metal casting is laser pretreated, so that the surface roughness of the metal casting can be greatly improved, which has an inhibitory effect on the crack propagation at the interface, and the rough surface can effectively inhibit the splashing of molten droplets during thermal spraying, reducing the possibility of small pore defects, thereby reducing the generation of crack sources and improving the bonding strength between the coating and the metal casting. Compared with the existing sandblasting pretreatment, the surface morphology of the metal casting after laser pretreatment is more controllable, the wetting effect on the thermal spray ions is stronger, the porosity at the interface is lower, and the thermal spray coating prepared by the sharper surface morphology processed by laser pretreatment is embedded or bite-type, and the bonding strength with the metal casting is higher, and the service life of the coating is longer.
[0012] After laser pretreatment, a thermal spraying process is used to thermally spray the surface of the metal casting to obtain a coating with a thickness of 100-150 μm. The thermal spraying process can be a commonly used thermal spraying technology in the field such as supersonic flame spraying, arc melting spraying, and plasma spraying. The inventor uses arc melting spraying as an example in this application. The voltage of the arc melting spraying is 27-33V, the current is 130-170A, the atomizing air pressure is 0.4-0.6MPa, the melting spraying distance is 120-180mm, and the wire material is Ni-Cu alloy wire. Then, a sealant is applied on the surface of the coating with a coating thickness of 0.5-1.5mm. After that, circulating air pressure and ultrasonic treatment are used to allow the sealant to penetrate into the pores at the bottom of the coating as much as possible, thereby achieving the effect of sealing the interconnected pores and surface pores in the coating after curing, greatly reducing the porosity inside the coating and improving the bonding strength between the coating and the metal casting. In addition, the excess sealant on the surface of the coating can also be transformed into a dense film, which prevents the corrosive medium from penetrating the coating and directly corroding the metal casting.
[0013] In summary, the present application adopts laser pretreatment before the thermal spraying process and further adopts circulating air pressure and ultrasonic treatment to assist the sealing agent for sealing treatment after the thermal spraying process, which greatly reduces the possibility of particle shedding on the coating surface and overall peeling and failure of the coating, improves the corrosion resistance of the coating, extends the service life of the coating, and improves the thermal spray coating's ability to repair and strengthen metal castings.
[0014] Preferably, in step S3, the sealing agent is an organic / inorganic composite sealing agent.
[0015] By adopting the above-mentioned technical scheme, the present application further adopts an organic / inorganic composite sealer, which can have both the high permeability of the organic sealer and the high temperature resistance of the inorganic sealer, further improving the sealing effect of the sealer on the thermal spray coating and the heat-resistant corrosion performance of the sealer.
[0016] Preferably, the organic / inorganic composite sealing agent comprises a modified silicone rubber matrix, an inorganic filler, a curing agent and a catalyst in a weight ratio of 200:(20-50):3:1.
[0017] Preferably, the organic / inorganic composite sealing agent comprises a modified silicone rubber matrix, an inorganic filler, a curing agent and a catalyst in a weight ratio of 200:50:3:1.
[0018] By adopting the above-mentioned technical scheme, the present application optimizes the ratio between the modified silicone rubber matrix and the inorganic filler, so that the prepared sealing agent has good sealing effect and heat-resistant corrosion performance. Experiments have shown that when the weight ratio between the modified silicone rubber matrix, the inorganic filler, the curing agent and the catalyst is 200:50:3:1, the thermal weight loss of the prepared sealing agent is small, and the sealing effect and heat-resistant corrosion performance are better.
[0019] Preferably, the modified silicone rubber matrix comprises silicone rubber and isocyanate resin in a weight ratio of 1:(0.5-1.2).
[0020] Preferably, the modified silicone rubber matrix comprises silicone rubber and isocyanate resin in a weight ratio of 1:1.
[0021] By adopting the above technical scheme, the present application adopts isocyanate resin to modify silicone rubber, which can further improve the heat resistance of silicone rubber. At the same time, silicone rubber can also be beneficial to the curing of isocyanate resin. The two give full play to the synergistic effect between each other, so that the sealing agent has better heat resistance and sealing ability. And it has been proved by experiments that when the weight ratio of silicone rubber and isocyanate resin is 1:1, the heat resistance and sealing ability of the sealing agent are better. This is because as the lifting effect of isocyanate resin on silicone rubber reaches its limit, continuing to increase the amount of isocyanate resin will only gradually weaken the binding effect of silicone rubber on isocyanate resin, increase the tendency of isocyanate resin precipitation, and deteriorate the dispersion. The silicone rubber of the present application is terminal hydroxyl polysiloxane, specifically 107 silicone rubber. The isocyanate resin of the present application is bisphenol A type isocyanate resin. The curing agent of the present application is ethyl orthosilicate. The catalyst of the present application is dibutyltin dilaurate.
[0022] Preferably, the inorganic filler is kaolin or a mixture of kaolin and one of fumed silica and nano-alumina powder.
[0023] Preferably, the inorganic filler is kaolin.
[0024] By adopting the above technical solution, the present application adopts kaolin as an inorganic filler, or mixes kaolin with one of fumed silica and nano-alumina powder as an inorganic filler, and adds it to the modified silicone rubber matrix, which significantly improves the thermal stability of the sealing agent in a hot corrosion environment and the adhesion to the thermal spray coating, thereby improving the sealing effect. And experiments have shown that under the condition of a certain amount of filler, the sealing agent made of kaolin has a stronger ability to resist heat corrosion.
[0025] Preferably, in the step S1, the laser pretreatment is specifically: first performing one laser cleaning, then performing 3-4 laser etchings, and finally performing one more laser cleaning, wherein the scanning paths of the laser cleaning and the laser etching are perpendicular.
[0026] By adopting the above-mentioned technical solution, the present application adopts a laser pretreatment method combining laser cleaning and laser etching. Compared with only laser cleaning or only laser etching, it can not only make the surface of the metal casting have a higher roughness, but also increase the number of anchor points between the surface of the metal casting and the thermal spray coating, reduce the existence of spreading interface bonding, and increase embedded or bite-type interfaces, thereby improving the bonding strength between the thermal spray coating and the metal casting.
[0027] Preferably, the curing in step S3 is step-by-step curing, specifically: first curing at room temperature for 46-48 hours, and then curing at a temperature of 180-190° C. for 2-2.5 hours.
[0028] In summary, this application has the following beneficial technical effects:
[0029] 1. This application adopts laser pretreatment before the thermal spraying process and further adopts circulating air pressure and ultrasonic treatment to assist the sealing agent for sealing treatment after the thermal spraying process, which greatly reduces the possibility of particle shedding on the coating surface and overall peeling failure of the coating, improves the corrosion resistance of the coating, extends the service life of the coating, and enhances the thermal spraying process The repair and strengthening ability of superficial defects of metal castings;
[0030] 2. The present application adopts modified silicone rubber matrix, inorganic filler, curing agent and catalyst to prepare organic / inorganic composite sealer, which can have both high permeability of organic sealer and high temperature resistance of inorganic sealer, so that the sealer has strong heat corrosion resistance and has better sealing effect on thermal spray coating;
[0031] 3. The present application adopts a laser pretreatment method that combines laser cleaning and laser etching. Compared with laser cleaning alone or laser etching alone, it can not only make the surface of the metal casting have a higher roughness, but also increase the number of anchor points between the surface of the metal casting and the thermal spray coating, reduce the existence of spreading interface bonding, and increase embedded or bite-type interfaces, thereby improving the bonding strength between the thermal spray coating and the metal casting. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Unless otherwise specified, the raw materials used in this application are all commercially available products, including:
[0034] The size of the metal casting is 100mm×100mm×6mm;
[0035] The Ni-Cu alloy wire contains 65wt% Cu, 6wt% Mn, 2wt% Si, and the rest Ni and other unavoidable impurities.
[0036] 107 silicone rubber, purchased from Shandong Qiyun Chemical Co., Ltd.;
[0037] Bisphenol A type isocyanate resin, purchased from Yangzhou Tianqi New Materials Co., Ltd., model 500t-a;
[0038] Kaolin, purchased from Lingshou County Shuangshi Mineral Products Co., Ltd., with a particle size of 325 μm;
[0039] Fumed silica, purchased from Degussa, model A200, particle size 8 μm;
[0040] Nano-alumina powder, purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 30 nm;
[0041] Tetraethyl orthosilicate, purchased from Jinan Shuangying Chemical Co., Ltd., with a Si content of 28%;
[0042] Dibutyltin dilaurate was purchased from Shandong Yunxin New Material Technology Co., Ltd. with a content of 18%.
[0043] Example 1
[0044] A thermal spray strengthening remanufacturing method for shallow defects of metal castings, comprising the following steps:
[0045] S1. First, the surface of the metal casting is degreased and derusted with acetone, then cleaned and dried, and then laser cleaned once, then laser etched three times, and finally laser cleaned once. The laser power of the laser cleaning is 10W, the frequency is 20kHz, and the scanning speed is 1000mm / s. The laser power of the laser etching is 60W, the frequency is 20kHz, and the scanning speed is 200mm / s. S2. Under the conditions of voltage of 27V, current of 130A, atomizing air argon gas of 0.4MPa, and spraying distance of 120mm, arc spraying equipment is used to perform arc spraying on the metal casting treated in step S1 to form a coating with a thickness of 100μm on the surface of the metal casting, wherein the wire material treated by arc spraying is Ni-Al alloy wire;
[0046] S3. First, 133.33 kg of 107 silicone rubber and 66.67 kg of bisphenol A type isocyanate resin were mixed at a temperature of 80°C, and 3 kg of ethyl orthosilicate, 1 kg of dibutyltin dilaurate and 20 kg of kaolin were added and mixed evenly, and then coated on the coating surface with a coating thickness of 0.5 mm. After that, the substrate was ultrasonically vibrated for 1 hour under vacuum-pressure-vacuum cycle pressure, wherein the vacuum environment was maintained for 5 minutes, and the container was evacuated to 30 Pa, and finally cured at room temperature for 46 hours, and then cured at 180°C for 2.5 hours to complete the sealing treatment.
[0047] Example 2
[0048] A thermal spray strengthening remanufacturing method for shallow defects of metal castings, comprising the following steps:
[0049] S1. First, the surface of the metal casting is degreased and derusted with acetone, then cleaned and dried, and then laser cleaned once, then laser etched four times, and finally laser cleaned once. The laser power of the laser cleaning is 10W, the frequency is 20kHz, and the scanning speed is 1000mm / s. The laser power of the laser etching is 60W, the frequency is 20kHz, and the scanning speed is 200mm / s. S2. Under the conditions of voltage of 33V, current of 170A, atomizing air argon gas of 0.6MPa, and spraying distance of 180mm, arc spraying equipment is used to perform arc spraying on the metal casting treated in step S1 to form a coating with a thickness of 150μm on the surface of the metal casting, wherein the wire material treated by arc spraying is Ni-Al alloy wire;
[0050] S3. First, 133.33 kg of 107 silicone rubber and 66.67 kg of bisphenol A type isocyanate resin were mixed at a temperature of 80°C, and 3 kg of ethyl orthosilicate, 1 kg of dibutyltin dilaurate and 20 kg of kaolin were added and mixed evenly, and then coated on the coating surface with a coating thickness of 1.5 mm. After that, the substrate was ultrasonically vibrated for 1.5 hours under vacuum-pressure-vacuum cycle pressure, wherein the vacuum environment was maintained for 10 minutes, and finally cured at room temperature for 48 hours, and then cured at 190°C for 2 hours to complete the sealing treatment.
[0051] Example 3
[0052] A thermal spray strengthening and remanufacturing method for shallow defects of metal castings is different from Example 2 in that: in step S3, the amount of kaolin added is 35 kg, and the rest is the same as Example 2.
[0053] Example 4
[0054] A thermal spray strengthening and remanufacturing method for shallow defects of metal castings is different from Example 2 in that: in step S3, the amount of kaolin added is 50 kg, and the rest is the same as Example 2.
[0055] Example 5
[0056] A thermal spray strengthening remanufacturing method for shallow defects of metal castings, which is different from Example 4 in that 50 kg of kaolin is replaced by a mixture of 40 kg of kaolin and 10 kg of fumed silica, and the rest is the same as Example 4.
[0057] Example 6
[0058] A thermal spray strengthening remanufacturing method for shallow defects of metal castings is different from Example 4 in that 50 kg of kaolin is replaced by a mixture of 40 kg of kaolin and 10 kg of nano-alumina powder, and the rest is the same as Example 4.
[0059] Example 7
[0060] A thermal spray strengthening and remanufacturing method for shallow defects of metal castings is different from Example 2 in that: in step S3, the weight ratio of 107 silicone rubber and bisphenol A type isocyanate resin is 1:0.7, wherein the 107 silicone rubber is 117.65 kg, and the bisphenol A type isocyanate resin is 82.35 kg, and the rest is the same as Example 2.
[0061] Example 8
[0062] A thermal spray strengthening and remanufacturing method for shallow defects of metal castings, which is different from Example 2 in that: in step S3, the weight ratio of 107 silicone rubber and bisphenol A type isocyanate resin is 1:1, wherein the 107 silicone rubber is 100 kg, and the bisphenol A type isocyanate resin is 100 kg, and the rest is the same as Example 2.
[0063] Example 9
[0064] A thermal spray strengthening and remanufacturing method for shallow defects of metal castings is different from Example 2 in that: in step S3, the weight ratio of 107 silicone rubber and bisphenol A type isocyanate resin is 1:1.2, wherein the 107 silicone rubber is 90.91 kg and the bisphenol A type isocyanate resin is 109.09 kg, and the rest is the same as Example 2.
[0065] Comparative Example 1
[0066] The difference from Example 2 is that the laser pretreatment in step S1 is replaced by sandblasting pretreatment, and the sandblasting pretreatment is carried out by a sandblasting machine. The sand type used in the sandblasting machine is brown corundum, the sandblasting pressure is 0.7 MPa, the sandblasting angle is 90°, the sandblasting distance is 100 mm, and the sandblasting time is 5 s. The rest is the same as Example 2.
[0067] Comparative Example 2
[0068] The difference from Example 2 is that in step S1, only two laser cleanings are used to pre-treat the surface of the metal casting, and the rest is the same as Example 2.
[0069] Comparative Example 3
[0070] The difference from Example 2 is that in step S1, only four laser etchings are used to pre-treat the surface of the metal casting, and the rest is the same as Example 2.
[0071] Comparative Example 4
[0072] The difference from Example 2 is that step S3 is removed, and the thermal spraying is not subjected to pore sealing treatment. The rest is the same as Example 2.
[0073] Comparative Example 5
[0074] The difference from Example 2 is that in step S3, 20 kg of kaolin is not added, and only 146.67 kg of 107 silicone rubber and 73.33 kg of bisphenol A type isocyanate resin are used, and the rest is the same as Example 2.
[0075] Comparative Example 6
[0076] The difference from Example 2 is that in step S3, 220 kg of sodium silicate solution is used as a sealing agent to seal the thermal spray coating, and the rest is the same as Example 2.
[0077] Comparative Example 7
[0078] The difference from Example 2 is that in step S3, 66.67 kg of bisphenol A type isocyanate resin is not added, and only 200 kg of 107 silicone rubber is used. The rest is the same as Example 2.
[0079] Comparative Example 8
[0080] The difference from Example 2 is that in step S3, circulating gas pressure is not used, the container is only evacuated to 30 Pa, and ultrasonic treatment is performed under vacuum conditions. The rest is the same as Example 2.
[0081] Performance Testing
[0082] 1. The cross-sectional microstructures of the coatings of the above-mentioned embodiments and comparative examples were observed using a ZEISS Axi Observer A3 metallographic microscope, and the porosity of the coatings was measured using Image J quantitative analysis software. The results are shown in Table 1.
[0083] 2. Referring to the method in GB / T 8642-2002 "Determination of tensile bonding strength of thermal spraying", a universal testing machine (C45.105, MTS, China) was used to measure the bonding strength of the coatings of the above embodiments and comparative examples. The test conditions were: a tensile rate of 2 mm / min and a test temperature of room temperature. Before the test, the side of the sample that was not subjected to arc spraying and the surface of the pull rod pair were first sandblasted, and then E-7 high temperature structural adhesive (E-7, Shanghai Huayi Resin Co., Ltd.) was used as an adhesive to bond the sample to the pull rod pair, and the sample was cured at a constant temperature of 120°C for 2 hours, and then cooled to room temperature and tested again. The results are shown in Table 1.
[0084] 3. In a 3.5wt% NaCl solution simulating seawater medium, the corrosion resistance of the coatings of the above embodiments and comparative examples was electrochemically tested using a PARSTAT2273 electrochemical workstation; before the test, the coatings were cleaned and degreased with alcohol using an ultrasonic cleaner and dried in air. The sample electrode was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire was used as the counter electrode. To ensure the accuracy of the measurement, the remaining surface was covered with an epoxy resin gasket, leaving about 1 cm 2 The coating area was exposed to 3.5wt% NaCl solution, and the corrosion potential was calculated at the intersection of the linear fits of the anodic and cathodic polarization curves according to the Tafel extrapolation method. The results are shown in Table 1.
[0085] 4. Prepare a mixed aqueous solution of sodium sulfate and potassium sulfate with a molar ratio of 7:3 and a concentration of 2 mol / L, and apply it to the coating surface of the above embodiment and comparative example at a concentration of 3-5 mg / cm 2 The amount of sulfate on the coating surface is controlled by the amount of sulphate. The sample is then placed in a muffle furnace and the temperature is set to 400-450°C. One cycle is 5 hours. A total of 6 cycles are performed. The weight of each sample before and after each cycle is recorded and the corresponding corrosion rate (mg / cm 2 ), and the results are shown in Table 1.
[0086] Table 1 Performance test results
[0087]
[0088] As can be seen from Table 1, the coating porosity of the embodiment of the present application is only 4.59-5.15%, the bonding strength with the metal casting reaches 53.42-55.13MPa, the corrosion potential under electrochemical corrosion conditions is only -0.438~-0.487V, and the thermal corrosion rate under thermal corrosion conditions is only 11.67-12.46mg / cm 2 The experimental data show that the coating formed on the surface of the metal casting by the present application has a low porosity, a high bonding strength with the surface of the metal casting, and excellent electrochemical corrosion resistance and heat corrosion resistance. It is not prone to overall peeling failure and has a strong ability to repair and strengthen superficial defects of metal castings.
[0089] Among them, the difference between Example 3-4 and Example 2 is that the amount of inorganic filler added to the sealing agent in step S3 is different. It can be seen from Table 1 that the porosity of Example 3-4 is lower than that of Example 2, the bonding strength is higher than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are lower than those of Example 2. In addition, Example 4 has the lowest porosity, the highest bonding strength, and the lowest corrosion potential and thermal corrosion rate under electrochemical conditions. The experimental results show that the increase in the amount of inorganic filler added can improve the thermal stability of the sealing agent in a hot corrosion environment and the adhesion to the thermal spray coating, thereby enhancing the sealing effect. In addition, when the weight ratio of 107 silicone rubber, kaolin, ethyl orthosilicate and dibutyltin dilaurate is 200:50:3:1, the sealing agent has a better sealing effect.
[0090] The difference between Example 5-6 and Example 4 is that the same amount of kaolin added is replaced by a mixture of kaolin and one of fumed silica and nano-alumina powder. It can be seen from Table 1 that the porosity of Example 5-6 is greater than that of Example 4, the bonding strength is lower than that of Example 4, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than that of Example 4. The experimental results show that, at the same addition amount, adding kaolin as an inorganic filler to the sealing agent can further improve the sealing effect of the sealing agent.
[0091] The difference between Example 7-9 and Example 2 is that the ratio of 107 silicone rubber and bisphenol A type isocyanate resin is different. It can be seen from Table 1 that the porosity of Example 7-8 is lower than that of Example 2, the bonding strength is higher than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are lower than those of Example 2. Although the effect of Example 9 is stronger than that of Example 2, it is slightly worse than that of Example 7-8. The experimental results show that under the condition of a certain total amount, with the increase of the addition amount of bisphenol A type isocyanate resin, the sealing effect of the sealing agent shows a trend of first increasing and then decreasing, and the sealing agent has a better sealing effect when the weight ratio of the two is 1:1.
[0092] The difference between Comparative Example 1 and Example 2 is that sandblasting pretreatment is used instead of laser pretreatment. It can be seen from Table 1 that the porosity of Comparative Example 1 is greater than that of Example 2, the bonding strength is lower than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than those of Example 2. The experimental results show that the present application uses laser pretreatment instead of sandblasting pretreatment, which can further improve the repair and strengthening effect of the thermal spraying process on metal castings.
[0093] The difference between Comparative Example 2-3 and Example 2 is that only laser cleaning or laser etching is used in the laser pretreatment. It can be seen from Table 1 that the porosity of Comparative Example 2-3 is greater than that of Example 2, the bonding strength is lower than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than those of Example 2. The experimental results show that the combination of laser cleaning and laser etching adopted in the present application can take advantage of the respective advantages of the two, thereby further improving the repair and strengthening effect of the thermal spraying process on metal castings.
[0094] The difference between Comparative Example 4 and Example 2 is that the thermal spray coating is not sealed. It can be seen from Table 1 that the porosity of Comparative Example 4 is greater than that of Example 2, the bonding strength is lower than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than those of Example 2. The experimental results show that the present application further adopts a sealing treatment after the thermal spraying process, which can further improve the repair and strengthening effect of the thermal spraying process on metal castings.
[0095] The difference between Comparative Examples 5-6 and Example 2 is that the sealing treatment uses only organic sealing agents or inorganic sealing agents. It can be seen from Table 1 that the porosity of Comparative Examples 5-6 is greater than that of Example 2, the bonding strength is lower than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than those of Example 2. The experimental results show that the organic / inorganic composite sealing agent used in this application can combine the advantages of both, so that the sealing agent has better heat corrosion resistance, thereby further improving the sealing effect of the sealing agent, and then improving the repair and strengthening effect of the thermal spraying process on metal castings.
[0096] The difference between Comparative Example 7 and Example 2 is that bisphenol A type isocyanate resin is not used in the sealing agent to modify the 107 silicone rubber. It can be seen from Table 1 that the porosity of Comparative Example 7 is greater than that of Example 2, the bonding strength is lower than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than those of Example 2. The experimental results show that the present application uses bisphenol A type isocyanate resin to modify the 107 silicone rubber, which can give full play to the synergistic effect of the two, thereby further improving the sealing effect of the sealing agent, and then improving the repair and strengthening effect of the thermal spraying process on metal castings.
[0097] The difference between Comparative Example 8 and Example 2 is that circulating air pressure is not used in the sealing treatment, and only vacuum ultrasonic treatment is used. It can be seen from Table 1 that the porosity of Comparative Example 8 is greater than that of Example 2, the bonding strength is lower than that of Example 2, and the corrosion potential and thermal corrosion rate under electrochemical conditions are higher than those of Example 2. The experimental results show that the present application adopts the method of circulating air pressure combined with ultrasonic treatment to further improve the sealing effect of the sealing agent, thereby improving the repair and strengthening effect of the thermal spraying process on metal castings.
[0098] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A thermal spray strengthening and remanufacturing method for shallow defects of metal castings, characterized in that: The following steps are involved: S1. Degreasing, cleaning and laser pretreatment of the metal casting surface; S2. A thermal spray coating is prepared on the surface of the metal casting treated in step S1 by a thermal spraying process; S3. The organic / inorganic composite sealing agent is applied to the coating surface, and then ultrasonically treated under vacuum-pressure-vacuum cycle pressure for 1-1.5 hours, wherein the vacuum environment is maintained for 5-10 minutes, and then the sealing treatment is completed by curing; The organic / inorganic composite sealing agent comprises a modified silicone rubber matrix, kaolin, a curing agent and a catalyst in a weight ratio of 200:(20-50):3:1; The modified silicone rubber matrix comprises silicone rubber and isocyanate resin in a weight ratio of 1:1; The laser pretreatment is specifically as follows: firstly, laser cleaning is performed once, then laser etching is performed 3-4 times, and finally, laser cleaning is performed once more, wherein the scanning paths of laser cleaning and laser etching are perpendicular.
2. The thermal spray strengthening remanufacturing method for shallow defects of metal castings according to claim 1, characterized in that: The organic / inorganic composite sealing agent comprises a modified silicone rubber matrix, kaolin, a curing agent and a catalyst in a weight ratio of 200:50:3:
1.
3. The thermal spray strengthening remanufacturing method for shallow defects of metal castings according to claim 1, characterized in that: The curing in step S3 is step-by-step curing, specifically: first, curing at room temperature for 46-48 hours, and then curing at a temperature of 180-190° C. for 2-2.5 hours.
Citation Information
Patent Citations
Abrasion-resistant iron-based amorphous coating hole sealing agent, preparation method, hole sealing method and hole sealing device
CN112194960A
High-temperature-resistant hole sealing agent for hot-dip plating sink roll as well as preparation method and coating method of high-temperature-resistant hole sealing agent
CN113072826A
Thermal spraying reinforced repair method for superficial defects of metal casting
CN114959543A
Pretreatment method for high-interface-strength heavy-duty coating surface of aluminum alloy storage tank
CN118086992A